Efficiency of KOH-activated carbon for removal of heavy metal pollution from water - Byamba-Ochir, Narandalai; Muratbyek, Nazgul; Tumen-Ulzii, Narangarav; Alyeksandr, Ariunaa; Oyunchimeg, Nasantogtokh (Mongolian Journal of Chemistry, 2022)
The study to reduce heavy metals pollution from water using the KOH-activated carbon was studied the factors affecting the adsorption capacities of Cu(II) and Pb(II), in particular, initial metals concentration, pH of the solution, and contact time in static conditions. Using X-ray photoelectron spectroscopy and FTIR analysis to determine the elemental composition and surface functional groups of the activated carbon surface, the presence of oxygen-related functional groups was observed. The maximum adsorption capacities were 135.8 mg g-1 and 31.0 mg g-1 for removal of lead and copper solutions with the initial concentration of 300 mg L-1 of metal at 318 K, respectively. The removal percentage was found to be higher for Pb (II) when compared with Cu (II).